Spiral Slotted Microstrip Antenna Design for 700 MHz Band Application - Ricardo Meneses González; R. Linares y Miranda; R. Leyva Hernández (International Journal of Antennas and Propagation)
This work describes the design and implementation of spiral slotted microstrip antenna. Recently, just like other countries, in Mexico, terrestrial digital television has been implemented (analogic shutdown); as a consequence, the 700 MHz UFH Band (698–806 MHz) has been opened to new telecommunications services, particularly wireless mobile communication. This technological advance represents a radio mobile antenna design challenge because it is necessary to design an antenna whose dimensions must be small enough, which satisfies gain, resonance frequency, and bandwidth requirements and is of low cost.